Logística y productividad de los trabajadores del área de logística de la Municipalidad Distrital de San Juan Bautista 2024 - Cuespan Camus, Darwin Alexis (2025)
The determination to relate the variable: logistics management and the productivity of workers in the logistics area of the District Municipality of San Juan Bautista in 2024, was the objective of this study, quantitatively adopting the approach, a design that avoids the experimental and a descriptively correlational character. The data was collected cross-sectionally, analyzing the current nature of the variables. In the end, it was shown that Cronbach's Alpha was 0.972** for logistics management and 0.962** for productivity, indicating high internal consistency in both variables. A Pearson correlation of 0.885** was found between logistics management and productivity, with a significance value of 0.000, confirming a significantly positive link and significant at the 0.01** level. The perception of logistics management was mostly medium, with 40% of respondents, while productivity was evaluated as high by 46.7%. This research highlights the importance of establishing effective logistics practices as a strategy to optimize labor productivity in the municipal context.